Pengaruh Pembayaran melalui Metode Paylater Terhadap Minat Belanja Mahasiswa: (Studi Kasus:Universitas Islam Negri Sultan maulana Hasanuddin banten) - Desty Anggraini (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The emergence of new payment methods such as Paylater makes shopping easier and increases consumers' shopping interest. This research aims to find out how much influence the paylater payment method has on students' shopping interest. The method used in this research is a quantitative method. Based on the results of the T Test and F Test, the variable "Payment via Paylater Method" (X) has a significant influence on the variable "Shopping Interest" (Y), with a value of sig. 0.05 < X value (3.442) and calculated F value 11.850 > F table 4.10. From this research regarding the influence of paylayer on student shopping interest, it can be concluded that the payment system via the paylater method has a significant effect on student shopping interest.